Comparative Study of a Simulated and Real Life Reliability of Turbine Gas Path Diagnostics (International Journal of Innovative Research in Engineering & Management, 2023)
Enhancing the performance of gas turbine  requires the bringing together and optimization of the  disciplines and expertise required to acquire an  operationally competitive gas turbine engine. This study  comprises comparative research between simulated and  actual reliability of the gas path of a turbine engine. An  innovative idea was introduced to reduce the gap between  diagnostics processes via simulation and actual  maintenance condition of the engine. The possible sources  of errors were investigated by generating real error  distribution. This research study explores the comparative  investigation conducted to evaluate the reliability of a  turbine gas path through simulating varying scenarios and  analyzing real-life performance data. The application of  simulation tools is to enable the replication of operating  conditions and accurately model the gas turbine  components, providing insights into potential weaknesses  and strength. Real-life performance data provides important  information about actual system behavior, including the  frequency and nature of failures. Comparative  investigations allow for validation of simulation accuracy,  refinement of models, and identification of discrepancies.  The findings from these investigations contribute to the  optimization of gas turbine reliability, leading to efficient,  cost effective power generation systems.
Keywords: Diagnostics; Enhancement; Gas Turbine; Gas Path Analysis; Simulation